Analysis and Evaluation of Internal Control Accounting Information System for Purchase of Merchandise and Cash Disbursements at PT Bali Kulina Utama According to the COSO Framework Approach - Nyoman Tri Krismahayani; I Ketut Parnata; I Ketut Suwintana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
This study aims to evaluate the internal control of the accounting information system for the purchase of merchandise inventory and cash disbursements at PT Bali Kulina Utama. The results of this study are expected to provide constructive suggestions in improving the implementation of controls that can minimize the potential for fraud and fraud in the company's activities at PT Bali Kulina Utama. This type of research is a case study using two types of data, namely primary data and secondary data. Data collection techniques used are observation, interviews and documentation. The analytical technique used is descriptive analysis technique, namely by explaining the accounting information system for the purchase of merchandise inventory and cash disbursements and comparative analysis techniques, namely by comparing the implementation of internal control accounting information systems at PT Bali Kulina Utama with the theory of internal control according to the COSO Framework approach. The results of this study indicate that the accounting information system for the purchase of merchandise inventory and cash disbursements has three activities originating from ordering, receiving, storing and disbursing cash. The results of the evaluation of the implementation of the accounting information system internal control at PT Bali Kulina Utama are not fully in accordance with the five components of the COSO Fraework internal control. Four of the five components that are not in accordance with the COSO Framework are the internal control environment, risk assessment and risk response, control and monitoring activities. An adequate component is the information and communication component.